Persepsi Mahasiswa Terhadap Integrasi Filosofi Pendidikan dalam Kurikulum Pendidikan Jasmani di Program Studi Pendidikan Olahraga - Jamaludin (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aims to analyze students' perceptions of the integration of educational philosophy into the physical education curriculum at the Mandalika Education Study Program. Using a descriptive quantitative approach, data were collected through closed-ended questionnaires employing a 5-point Likert scale. The results show that the majority of students (59.26%) perceive educational philosophy as significantly relevant to their understanding of physical education, with a dominant score of 4.0. Additionally, 46.43% of respondents stated that educational philosophy greatly contributes to their personal development and character formation. However, the presence of outlier data, such as scores of 103.0 and 107.0, requires further review to ensure the validity of the analysis. Overall, these findings emphasize the importance of integrating educational philosophy into practical learning to establish a foundation for critical thinking, reflective reasoning, and character development among students. This study recommends a more comprehensive curriculum evaluation and pedagogical approaches focused on harmonizing theory and practice in physical education.